Guiana Francesa, janeiro de 1809: articulações para a construção governativa conforme as primeiras ordenanças - Ivete Machado de Miranda Pereira (Navigator)
In January 1809 the French Guiana was invaded by Portuguese troops from Grão-Pará, helped by the British Navy. This study intends to follow the beginning of the Portuguese administration in Guiana, precisely in the month of January 1809, through the first six Ordinances of the provisional governor, Manoel Marques, consulted in the Archives Nationales of Paris. In dialogue with this documentation, we will analyze Population and Temporary Administration of Cayenne’s Colony – Manoel Marques’s authorship – and the Capitulation signed between the defeated French governor and the conquerors, documents from the collection of the National Library of Rio de Janeiro. It is intended to understand how the Portuguese government immediately organized the new territory observing what had been stipulated in the surrender.